2005
DOI: 10.1007/s11199-005-8296-0
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Social Networks, and Contraceptive Use in Kenya

Abstract: The social network approach has recently come to aid our understanding of the ongoing fertility transition in developing countries. This study adds to the growing literature in situating the role of geography and interaction with significant others-community and family members-in understanding Kenya's puzzling fertility transition. Findings indicate that, contrary to previous findings that kin networks are conservative and against innovative fertility behavior, the respondent families, especially in the more p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 29 publications
3
21
0
Order By: Relevance
“…Instead, the strongest correlation between respondents and their alters on FP use seems to be with in-laws, and with sisters. This is consistent with some prior research that has identified kin networks as important influences on FP use, as kin are the ones with the highest stake in fertility outcomes (Musalia, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…Instead, the strongest correlation between respondents and their alters on FP use seems to be with in-laws, and with sisters. This is consistent with some prior research that has identified kin networks as important influences on FP use, as kin are the ones with the highest stake in fertility outcomes (Musalia, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…These results also established the influential role male partners and others, such as peers, relatives, or healthcare providers, play in decision making with regard to contraceptive use and choice in Africa [12,[48][49][50][51]. Power imbalances as a result of traditional socio-cultural norms, economic differences, and age disparities allow male partners to influence reproductive health decision making in patriarchal societies that exist in many Africa countries [52,53].…”
Section: Plos Onementioning
confidence: 85%
“…Social influence, like other mechanisms, can potentially hinder or help the adoption of positive reproductive behaviors [26]. Social influence may operate more powerfully within more homogeneous, dense, closed networks [13].…”
Section: Resultsmentioning
confidence: 99%